Contemporary Islamic philosophy response to reality and thinking outside history. Issue 1 (11th June 2019) - Othman Elkhosht, Mohamed
Abstract : Purpose: The purpose of this paper is to draw a map of the general features of epistemological and critical concerns in contemporary Islamic philosophy. This study will not be confined to the domain of academic philosophy or to those who are professionals in the field of philosophy. Design/methodology/approach: The paper adopted the critical rational approach in dealing with contemporary Islamic philosophy in the Arab world. The scope will include scholars from different fields of epistemology who tried to present a "vision" of the attitude that should be adopted in facing the challenges of the age and the problems of the nation on the epistemological level or the political, economic and social levels. Findings: There is a need for a philosophy of action and progress rather than a philosophy that is based on abstract ideas and theories and of words/rhetoric. The ethics required to accomplish this ought to identify the attributes of the citizen who can reach self-actualization through legitimate means based on a progress agenda with theoretical and philosophical foundations. Research limitations/implications: Because a critical rational approach can be dealt with from different perspectives, this paper will adopt the classification of the principal intellectual trends: the reformist, secular and liberal. Practical implications: This paper covers a long time span to determine whether the philosophical projects have been effective. Originality/value: This paper, which criticizes the philosophic projects that are theoretically unsound and that do not address real social problems (like poverty), argues the need for a philosophy of progress and action. This will lead to devising an agenda that addresses the challenges the society is facing and to finding alternative and creative solutions resulting in development.